2020
DOI: 10.4018/ijicte.2020040105
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of “The Internet of Things” Instruction in Technology Management, Cybersecurity, and Computer Science

Abstract: Many universities require end of course evaluations for all courses taught as tool for academic accreditation purposes. The reality is that often many academic departments either do not do anything or have no idea what to do when evaluations continue to be poor. As a result, students have fought back against this process to create their own on-line rating program, Rate My Professor.com, which allows students to give other students insights into who is a quality professor and who is not. This paper explores thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Internet facilities are a substantial factor in this study to determine the response and actions of the respondents related to the research questionnaire. It affects how people are aware of the internet as a supporting tool in learning [16]. The total population of 50 students from Saamasing, out of that, from the completed survey revealed that 58.…”
Section: Internet Facilities Qualitymentioning
confidence: 99%
“…Internet facilities are a substantial factor in this study to determine the response and actions of the respondents related to the research questionnaire. It affects how people are aware of the internet as a supporting tool in learning [16]. The total population of 50 students from Saamasing, out of that, from the completed survey revealed that 58.…”
Section: Internet Facilities Qualitymentioning
confidence: 99%
“…For nonmusic students, if they want to learn about folk music, they are more likely to enter the campus through the "intangible cultural heritage" art organized by the school and the elegant art into the campus. Teachers and students of colleges of music can regularly invite local folk artists, scholars, and experts to carry out the dissemination of music culture and the study of skills in this area by regularly adopt-ing the method of "going out and inviting in" [2]. It is also necessary to present the works adapted from local music culture through social activities and local activities, so that more people can know the charm of local music and generate higher social value.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the quality of cybersecurity with IoT, important steps can be taken against cyber-attacks. (Burrell et al, 2020).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%